Impact of assessment of bone status before corrective surgery of lumbar spine in patients over 50 years old - Banse C (Dove Medical Press, 2019)
Christopher Banse,1,2 Mourad Ould-Slimane,3 Emmanuel Foulongne,3 Alexis Perez,4 Gilles Avenel,1 Alain Daragon,1 Olivier Vittecoq11Rheumatology Department, Rouen University Hospital, 76000 Rouen, France; 2Rheumatology Department, Polyclinique Saint Côme, 60200 Compiègne, France; 3Department of Orthopaedic Surgery, Rouen University Hospital, 76000 Rouen, France; 4Department of Neurosurgery, Rouen University Hospital, 76000 Rouen, FranceBackground and objective: There is absence of data on the prevalence of osteoporosis before corrective surgery of the lumbar spine. We do not know the impact of bone assessment before corrective spine surgery, regarding the prevalence of osteoporosis, risk factors for osteoporosis, and prescription of osteoporotic treatment. Our objective was to evaluate the impact of assessment of bone status before corrective surgery of the lumbar spine.Methods: This retrospective study was conducted over a period of 30 months. Patients included were over 50 years old and had been referred to rheumatology consultation prior to corrective surgery of the lumbar spine with osteosynthesis, for scoliosis or spondylolisthesis. Assessment of bone status consisted in looking for risk factors for osteoporotic fracture, performing bone densitometry with the calculation of TBS (trabecular bone score) and the possible introduction of treatment for osteoporosis. Data were collected on complications related to bone fragility during follow-up.Results: Twenty-eight patients with a median age of 71.2 years (55.5–84.8) were included; 89% were women. T score was <−2.5 in 14.3% (4/28) and −1 to −2.5 in 42.9% (12/28) on at least one of the three sites analyzed. Fifty percent of patients had a TBS <1.2, a history of more than four falls per year, a duration of more than 20 s in the Timed Up and Go Test, and/or sedation treatment. Vitamin-calcium supplementation and treatment for osteoporosis were prescribed in 71.4% and 17.8% of cases, respectively. During follow-up, 3 patients had one or more osteoporotic vertebral fractures and 4 patients had loosening of implanted devices.Conclusion: Despite a low prevalence of densitometric osteoporosis and therapeutic management, one in four patients had a bone complication, suggesting the superiority of TBS as an indicator of bone status.Keywords: osteoporosis, spine surgery, bone evaluation, fracture, TBS